Global epidemiology of podoconiosis: A systematic review - Deribe, Kebede; Cano, Jorge; Trueba, Mei L.; Newport, Melanie J.; Davey, Gail (PLOS Neglected Tropical Diseases, 2018)
Background Podoconiosis is one of the few diseases that could potentially be eliminated within one generation. Nonetheless, the global distribution of the disease remains largely unknown. The global atlas of podoconiosis was conceived to define the epidemiology and distribution of podoconiosis through dedicated surveys and assembling the available epidemiological data. Methods We have synthesized the published literature on the epidemiology of podoconiosis. Through systematic searches in SCOPUS and MEDLINE from inception to February 14, 2018, we identified observational and population-based studies reporting podoconiosis. To establish existence of podoconiosis, we used case reports and presence data. For a study to be included in the prevalence synthesis, it needed to be a population-based survey that involved all residents within a specific area. Studies that did not report original data were excluded. We undertook descriptive analyses of the extracted data. This study is registered with PROSPERO, number CRD42018084959. Results We identified 3,260 records, of which 27 studies met the inclusion criteria. Podoconiosis was described to exist or be endemic in 32 countries, 18 from the African Region, 3 from Asia and 11 from Latin America. Overall, podoconiosis prevalence ranged from 0·10% to 8.08%, was highest in the African region, and was substantially higher in adults than in children and adolescents. The highest reported prevalence values were in Africa (8.08% in Cameroon, 7.45% in Ethiopia, 4.52% in Uganda, 3.87% in Kenya and 2.51% in Tanzania). In India, a single prevalence of 0.21% was recorded from Manipur, Mizoram and Rajasthan states. None of the Latin American countries reported prevalence data. Conclusion Our data suggest that podoconiosis is more widespread in the African Region than in the rest of the regions, although this could be related to the fact that most podoconiosis epidemiological research has been focused in the African continent. The assembled dataset confirms that comprehensive podoconiosis control strategies such as promotion of footwear and personal hygiene are urgently needed in endemic parts of Africa. Mapping, active surveillance and a systematic approach to the monitoring of disease burden must accompany the implementation of podoconiosis control activities.